Projecting Municipal Theme to Nollywood - Blessing Adjeketa (ELS Journal on Interdisciplinary Studies in Humanities, 2023)
Abstract This paper addresses the issue of municipal disposal, management, and its effect on Nigerians, and proposes municipal as a theme to Nollywood. The issue of improper solid waste (municipal) disposal and management and its effect on humans and the environment has been a subject of scholarly discussion for a very long time and in world the cinema. In Nigeria, the electronic media especially news bulletins present issues of improper waste disposal and its impact on community dwellers. However, there is yet a full-length feature film in Nigeria that deals primarily with the issue of municipals. Nollywood has over the years treated themes of varied identities such as prostitution, banditry, politics, and communal insecurity. However, it is pertinent to note that the most prominent studies on Nollywood films are on national identity and culture(s). There are nonetheless few studies on the culture of environmentalism or ecocriticism and health and illnesses in Nigerian films. The need for Filmmakers (practitioners) and scholars to do further studies into the field of solid waste identity (municipal) is indeed necessary. Therefore, in this paper, I reviewed materials on municipals, and films that treated issues revolving around municipals (garbage, rubbish, discards, junk) and their implications on humans and the environment in some films.